Synthesis and characterization of nanostructured aluminum borate by sol-gel method - Gupta, R. K.; Al-Ghamdi, A. A.; Al-Hartomy, Omar A.; Al-Hazmi, Faten; El-Tantawy, F.; Yakuphanoğlu, Fahrettin (Springer, 2012)
Nanostructured aluminum borate was synthesized using sol-gel technique. X-ray diffraction study revealed that the synthesized aluminum borate was single crystal. These nanorods have very uniform diameter. High-resolution transmission electron microscope images indicate that aluminum borate is well crystallized. The alternating current (AC) conductivity of the aluminum borate was studied as a function of temperature and frequency. The AC conductivity mechanism of the aluminum borate was found to be proportional to omega(s). The exponent s is almost independent with temperature. This suggests that AC conductivity mechanism of the aluminum borate can be interpreted by localized hopping model.
Keywords: Aluminum borate; Sol-gel; AC conductivity